2022
DOI: 10.1002/admi.202201442
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biomedical Application Opportunities of the Nanoparticle's Protein Corona

Abstract: with all three external dimensions in the nanoscale, whose longest and shortest axes do not differ significantly, with a significant difference typically being a factor of at least 3." This size allows nanoscale materials to be integrated into biomedical equipment since most biological systems are also nanoscale. [2] In addition to the definition of size, NPs used in biomedical research have a high degree of diversity in structure, chemical composition, morphology, hydrophobicity, surface chemistry, electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…However, there are other relevant classes of biological molecules (lipids, nucleic acids, metabolites), and a comprehensive view of the bio-nano interface requires us to also examine their role in the biomolecular corona and the ensuing biological responses, e.g., cell signaling and metabolism. [216,235] Lipids are insoluble in aqueous solvents and thus transported in blood as roughly spherical lipoprotein particles with sizes in the range <10-1000 nm, featuring a lipid core that is solubilized by surface functionalization with apolipoproteins. Little is known about the mechanisms through which these natural particles interact with synthetic NPs: Will lipoproteins attach to NPs as whole particles, or transfer their material, lipids and apolipoproteins, partially or completely to the NPs?…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other relevant classes of biological molecules (lipids, nucleic acids, metabolites), and a comprehensive view of the bio-nano interface requires us to also examine their role in the biomolecular corona and the ensuing biological responses, e.g., cell signaling and metabolism. [216,235] Lipids are insoluble in aqueous solvents and thus transported in blood as roughly spherical lipoprotein particles with sizes in the range <10-1000 nm, featuring a lipid core that is solubilized by surface functionalization with apolipoproteins. Little is known about the mechanisms through which these natural particles interact with synthetic NPs: Will lipoproteins attach to NPs as whole particles, or transfer their material, lipids and apolipoproteins, partially or completely to the NPs?…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also documented for ultrasmall gold NP (usGNP) evaluations. 92 2.2.2. Controllability.…”
Section: Intension and Extensionmentioning
confidence: 99%
“…However, the lesser cognition of PC (in comparison to other factors) has caused the exploration of in vivo fate to be more difficult. 90–92 Hence, it is essential to study and discover the formation behaviors and mechanisms of PC upon LNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al synthesised several NPs with similar shapes, sizes, and surface characteristics but different elasticity (45 kPa–760 MPa). After mixing these NPs with mouse plasma, they found that the composition of the protein corona formation changed non-monotonically with the increase in the elasticity of the NPs ( Li et al, 2022 ). For example, apolipoprotein AI was more likely to form the corona protein over NPs of intermediate elasticity (75–700 kPa).…”
Section: Protein Coronamentioning
confidence: 99%